Advancements in Medical Physics: The Role of Imaging Technologies in Modern Radiotherapy Techniques - Zhraa, Ameer Ali Awad Abad Al; Taher, Karrar Haider; Abdulhussein, Taisir Falah; Wahed, Saif Mayeh Abdel; Daham, Hanan Salem (American Journal of Botany and Bioengineering, 2025)
Advancements in medical physics have significantly enhanced the effectiveness of modern radiotherapy techniques, particularly through the integration of imaging technologies. Despite substantial progress, challenges remain in optimizing imaging modalities for accurate tumor targeting and reducing side effects. This study addresses the existing knowledge gap by analyzing the latest imaging innovations in radiotherapy and their impact on treatment precision. A qualitative methodology, including a review of clinical trials and technological assessments, was employed. Findings indicate that developments in imaging, such as MRI-guided radiotherapy and AI-assisted imaging analysis, have improved tumor delineation and minimized radiation exposure to healthy tissues. These advancements enhance patient outcomes and reduce treatment complications, making radiotherapy more efficient and accessible. The study underscores the need for continued interdisciplinary collaboration to refine imaging protocols and maximize clinical benefits.